SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SUPPLIER BUKU PADA TOGAMAS MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Leni Karlina (LPPM Universitas Mercu Buana Yogyakarta, 2020)
A selection of the best books’ supplier is very important in a bookstore, in producing books for their store. Sometimes, several books suppliers are difficult to choose, because many books suppliers from many regions, in which the selection is still manual. Such way causes a decision making which needs an accurate and precise calculation among the existed books suppliers. Therefore, researchers designed a decision support system for books suppliers’ selection, to be used by the TOGAMAS Bookstore in determining the books suppliers which will easily be selected, based on the specified criteria. This decision support system was created using the method of Simple Additive Weighting (SAW) as the tool that would help the TOGAMAS. The test was done by comparing the calculation from the TOGAMAS, with the calculation from the SAW, using 10 suppliers’ data to test the system performance. Based on the test, it was concluded that the percentage of the system performance was 50%.